SAT-511 Refractory Hypercalcemia Secondary to Antibiotic Eluting Calcium Sulphate Beads - Vora, Amy (J Endocr Soc, 2019)
Hypercalcemia secondary to placement of antibiotic eluting calcium sulphate beads is rare. We present the case of a 58 year old Caucasian woman who presented with altered mental status, septic shock and respiratory failure. Labs showed hypercalcemia. History revealed placement of antibiotic-eluting calcium sulphate beads after removal of her infected left prosthetic hip joint two days before presentation. She had no known history of calcium, parathyroid disorders, fractures or kidney stones. Total serum calcium was elevated to 12.2 mg/dl (Ref 8.4-10.2 mg/dl) on admission with peak levels two days later at 15.7mg/dl. Her intact PTH was < 10.0 pg/ml (Ref 15-65.0 pg/ml); 1,25 Dihydroxy Vitamin D was 8.9 pg/ml (Ref 18-78.0 pg/ml) and 25 Hydroxy Vitamin D was 13 pg/ml (Ref 30-80 pg/ml) thus ruling out primary hyperparathyroidism, granulomatous disease or Vitamin D toxicity as etiology. Multiple myeloma work up was negative and was on no medications known to cause hypercalcemia. She received 8 doses of calcitonin (4 units/kg) but due to her worsening kidney function (< 30 ml/min), she could not receive a bisphosphonate. She became volume overloaded and required dialysis which corrected her hypercalcemia and renal function. She received 8 days of continuous renal replacement therapy followed by 2 sessions of hemodialysis which improved her serum calcium levels and renal function to normal range. Mental status also improved with improvement in her calcium levels. Duration of elevated calcium levels was 5 days. After dialysis was stopped, her calcium level and creatinine remained normal. In this case, hypercalcemia was attributed to antibiotic-eluting calcium sulphate beads. This case represents a rare etiology of hypercalcemia. On review of the literature, very few cases have been reported in humans. The first report to describe hypercalcemia following placement of calcium sulphate beads in humans was a case series consisting of 15 patients. Out of these patients, 3 developed hypercalcemia, one of which developed symptoms and required treatment with intravenous fluids and bisphosphonates.(1) Another case reported a woman who suffered seizures due to a calcium leak into her cerebrospinal fluid after placement of calcium sulphate beads into her lumbar spine, however her serum calcium levels remained normal. (2) This case is one of a few reported in the literature of symptomatic hypercalcemia that occurred after placement of calcium sulphate beads. Further work is needed to understand those at risk of hypercalcemia from these agents. 1. Kallala R, Haddad FS. Hypercalcaemia following the use of antibiotic-eluting absorbable calcium sulphate beads in revision arthroplasty for infection. The bone & joint journal. 2015;97-b(9):1237-1241. 2. Smith I. Convulsions and Coma Associated with Iatrogenically Elevated CSF Calcium Levels Post Spinal Surgery: A Case Report. Crit Care Resusc. 2005;7(3):173-176.